All Days 2007
DOI: 10.2118/106798-ms
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermal Desorption Process Can Extend Life of Base Oil and Reduce Energy Costs

Abstract: In many cases, the primary waste management challenge facing operators is drilled cuttings generated using oil- or synthetic-based fluids (OBF, SBF). Low temperature thermal desorption units (TDUs) are commonly used treatment systems for removing oil from cuttings. The oil recovered from the thermal desorption process is often reused to make oil-based fluids. However, base oils change during the thermal desorption process, and these changes can have a detrimental impact on the performance of the base oil. In s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that LTTD is sufficient to treat OBDCs, wastes with light oils (Kapila and Thomas, 2003;Seaton et al, 2006). Besides, less inherent thermal degradation of the base oil in OBDCs under LTTD treatment, and thus recovered oil can be reused in the mud system (Fang et al, 2007). Falciglia et al (2011) environmental functions was enhanced after LTTD, indicating that LTTD could be a better alternate method compared to other harsh remediation processes.…”
Section: Thermal Treatmentmentioning
confidence: 99%
“…It has been demonstrated that LTTD is sufficient to treat OBDCs, wastes with light oils (Kapila and Thomas, 2003;Seaton et al, 2006). Besides, less inherent thermal degradation of the base oil in OBDCs under LTTD treatment, and thus recovered oil can be reused in the mud system (Fang et al, 2007). Falciglia et al (2011) environmental functions was enhanced after LTTD, indicating that LTTD could be a better alternate method compared to other harsh remediation processes.…”
Section: Thermal Treatmentmentioning
confidence: 99%